Secretion of intrinsic factor and hydrochloric acid after 12 weeks' treatment with cimetidine. Issue 4 (April 1978) - Epstein, O; Judelman, J; Bevan, G; Ardeman, S
Abstract : A sample of 16 patients had pentagastrin stimulation studies performed before starting a 12 week course of cimetidine, and again 12 hours after completing the course. Basal and pentagastrin stimulated intrinsic factor secretion was assayed in 13 patients. There was no significant difference in the pattern of secretion after 12 weeks' treatment with cimetidine. The basal and peak acid outputs of all 16 patients were measured. No significant difference was found in the pattern of acid secretion after treatment. It appears that parietal cell secretory function is restored to normal within 12 hours of discontinuing a prolonged course of cimetidine.